Arginine methylation of the c‐Jun coactivator RACO‐1 is required for c‐Jun/AP‐1 activation. (26th April 2013) - Davies, Clare C; Chakraborty, Atanu; Diefenbacher, Markus E; Skehel, Mark; Behrens, Axel
<x xml:space="preserve">Abstract</x> c‐Jun, the major component of the AP‐1 transcription factor complex, has important functions in cellular proliferation and oncogenic transformation. The RING domain‐containing protein RACO‐1 functions as a c‐Jun coactivator that molecularly links growth factor signalling to AP‐1 transactivation. Here we demonstrate that RACO‐1 is present as a nuclear dimer and that c‐Jun specifically interacts with dimeric RACO‐1. Moreover, RACO‐1 is identified as a substrate of the arginine methyltransferase PRMT1, which methylates RACO‐1 on two arginine residues. Arginine methylation of RACO‐1 promotes a conformational change that stabilises RACO‐1 by facilitating K63‐linked ubiquitin chain formation, and enables RACO‐1 dimerisation and c‐Jun interaction. Abrogation of PRMT1 function impairs AP‐1 activity and results in decreased expression of a large percentage of c‐Jun target genes. These results demonstrate that arginine methylation of RACO‐1 is required for efficient transcriptional activation by c‐Jun/AP‐1 and thus identify PRMT1 as an important regulator of c‐Jun/AP‐1 function.